The Role of Brand Love and Perceived Value in Building Generation Z Brand Loyalty: Evidence from Saisons Space Cirebon - Feby Nurul Fauzia; Misbak; Soesanty Maulany (Management Analysis Journal, 2026)
This study was motivated by the increasing competition in the coffee shop industry, which requires businesses to strengthen customer loyalty through the creation of superior value and emotional connections with consumers. Using a quantitative cross-sectional design and purposive sampling technique, this research involved 171 Generation Z consumers aged 17–28 years who were active members of Saisons Space Cirebon and had made at least two purchases within the previous three months. The collected data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that both brand love and perceived value have significant positive effects on brand loyalty, with perceived value emerging as the more dominant factor. Together, these variables explain 25.5% of the variance in consumer loyalty, indicating a moderate level of explanatory power. These findings suggest that consumer loyalty is shaped by a combination of rational considerations, such as perceived value, and emotional factors, such as attachment to the brand. The study contributes to the literature by integrating emotional and rational dimensions to explain Generation Z consumer loyalty in the context of local coffee shops. However, the cross-sectional quantitative approach may limit a deeper understanding of the emotional motivations underlying brand loyalty. Therefore, coffee shop businesses should prioritize strategies that enhance customer value and foster emotional relationships to maintain and strengthen customer loyalty.